2012
DOI: 10.1111/j.1755-148x.2012.00982.x
|View full text |Cite
|
Sign up to set email alerts
|

Inherited variants in the MC1R gene and survival from cutaneous melanoma: a BioGenoMEL study

Abstract: SummaryInherited MC1R variants modulate MITF transcription factor signaling, which in turn affects tumor cell proliferation, apoptosis, and DNA repair. The aim of this BioGenoMEL collaborative study in 10 melanoma cohorts was to test the hypothesis that inherited variants thereby moderate survival expectation. A survival analysis in the largest cohort (Leeds) was carried out adjusting for factors known to impact on survival. The results were then compared with data from nine smaller cohorts. The absence of any… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
103
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 69 publications
(111 citation statements)
references
References 52 publications
(59 reference statements)
3
103
3
Order By: Relevance
“…Mutations in exon 9 have not been reported in CMM. Immunohistochemical detection of KIT protein using anti-CD117 antibody does not reliably predict the KIT mutation status [31,96].…”
Section: Germline and Somatic Cmm Mutationsmentioning
confidence: 97%
See 1 more Smart Citation
“…Mutations in exon 9 have not been reported in CMM. Immunohistochemical detection of KIT protein using anti-CD117 antibody does not reliably predict the KIT mutation status [31,96].…”
Section: Germline and Somatic Cmm Mutationsmentioning
confidence: 97%
“…the epidermal growth factor receptor (EGFR), the Stem Cell-Like Factor (SCF) receptor KIT, Wnt/b-catenin, Notch, stromal cellderived factor-1 (SDF-1)/CXC Chemokine Receptor-4 (CXCR4) and vascular endothelial growth factor (VEGF)/VEGFR receptor [23,31,32]. Such growth factors cooperate and activate distinct parts of the tumorigenic downstream signalling paths and various Epithelial-Mesenchymal Transition (EMT)-associated molecules, including phosphatidylinositol 3'-kinase (PI3K)/Akt/ molecular target of rapamycin (mTOR), nuclear factor-kappa B (NF-kB), macrophage inhibitory cytokine-1 (MIC-1), vimentin, snail and twist [26].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have identified several genes and single nucleotide polymorphisms (SNPs) implicated in melanoma susceptibility that modulate melanoma outcome, such as, melanocortin 1 receptor (MC1R), the master regulator gene of human pigmentation, and the cyclin dependent kinase inhibitor 2A (CDKN2A), that codifies two proteins that work as tumor suppressors, p16 and p14ARF, regulating the cell cycle. MC1R is highly polymorphic and some of its functional variants are associated with increased risk of melanoma development and survival (34). Moreover, MC1R germinal mutation is associated with a higher somatic mutation burden (35), and it could be a predictive factor of response to immunotherapy with checkpoint inhibitors.…”
Section: Guess Labsmentioning
confidence: 99%
“…The study of RHC MC1R variants provided information about their association with other phenotypes and their effect on functioning of MSH-R has extended its role beyond pigmentation to diseased phenotypes. The MC1R variants, mainly the RHC alleles were also reported to be associated with increased risk of various types of melanoma [41] and UV induced susceptibility to skin damage [42]. The MC1R variants have been reported to be associated with pigmentary disorders including vitiligo [43], severe photoaging [44], congenital melanocytic nevi [45] and OCA [46].…”
Section: Oca6mentioning
confidence: 99%
“…The association of specific MC1R The variants I120T [41], V122M [50] and M128T [37,56] have been identified in the third transmembrane helix of MSH-R. The association of I120T with disease phenotype is not known however; it leads to a moderate decrease of cAMP production after stimulation with αMSH.…”
Section: The Mc1r Gene Variants Associated Phenotypes and Affects Onmentioning
confidence: 99%